The role of the community in tourism development in the Batu Katak ecotourism area, Bahorok district, Langkat regency - Sibarani, Claudina; Christin, Juan (Journal of Commerce, Management, and Tourism Studies, 2023)
The Batu Katak ecotourism area is an attractive tourism destination, with extraordinary natural beauty and biodiversity. Tourism development in this area cannot be separated from the active role and contribution of the local community. This study aims to describe the role of the community in tourism development in the BatuKatak ecotourism area.The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results of the study show that the community has a significant role in tourism development in the BatuKatak ecotourism area. First, the community plays a role in environmental preservation and management. Second, the community plays a role in empowering the local economy. Third, the community plays a role in tourism promotion and marketing. However, this research also found several challenges faced by the community in their role in developing tourism in the BatuKatak ecotourism area. These challenges include a lack of access to tourism education and training, a lack of understanding of the importance of environmental preservation, as well as a conflict of interest between the community and the developer. To overcome this challenge, this study recommends efforts by the government and related parties to provide tourism education and training to local communities, as well as to strengthen community participation in decision-making related to tourism development.